Women’s Costume in Modern Chinese Films: Stylistic Features - Li, Han; Alfоrova, Zoya (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article is devoted to the stylistic features of women’s costumes in modern Chinese cinema. The aim of the study is to identify the stylistic characteristics of women’s costumes in contemporary Chinese films. The research methodology combines general scientific approaches with methods of art criticism. In particular, the formal-stylistic analysis method was applied to examine the stylistic features of women’s costumes in modern Chinese cinema. Using the method of coloristic analysis, the article explores the materials and color palettes of costumes, which reflect specific stylistic solutions within the costume ensemble. The authors examine the main stylistic variations of women’s costume representations using examples from modern Chinese films across various genres. The traditional-historical style, strongly influenced by Emi Wada, is characterized by deeply symbolic use of color rooted in mythopoetic Chinese thought; the use of natural, flowing materials; inspiration from traditional Chinese garments; minimalist yet detailed design; and a kind of “choreography” of the costume, where garments are created with the characters’ movement in mind. The retro style draws on stylized interpretations of specific historical periods while incorporating modern cuts and, at times, contemporary materials. The urban style reflects cosmopolitan fashion trends, recognizable brands, and the use of modern textiles. In contrast, the futuristic style embraces cutting-edge materials, unconventional and often uncomfortable shapes, and technological or electronic accessories. It was found that each stylistic approach corresponds closely to the genre of the film, which in turn influences the design, choice of materials, and color scheme of women’s costumes. The study also reveals that within the Chinese film industry, certain conventional stylistic standards have developed for each costume type. It is noted that talented costume designers employ original methods and often draw on the experience of Western colleagues, particularly in co-productions.